2008
DOI: 10.1086/589848
|View full text |Cite
|
Sign up to set email alerts
|

The Contribution of AGNs and Star‐forming Galaxies to the Mid‐Infrared as Revealed by Their Spectral Energy Distributions

Abstract: We present the broadband SEDs of the largest available highly complete (72%) spectroscopic sample of MIRselected galaxies and AGNs at intermediate redshift. The sample contains 203 extragalactic sources from the 15 m ELAIS-SWIRE survey, all with measured spectroscopic redshift. Most of these sources have full multiwavelength coverage from the FUV (GALEX ) to the FIR (Spitzer) and lie in the redshift range 0:1 < z < 1:3. This large sample allows us for the first time to characterize the spectral properties of s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 24 publications
(4 citation statements)
references
References 73 publications
0
4
0
Order By: Relevance
“…Radio loud sources dominate the source counts down to levels of ∼1 mJy, however, at the sub-mJy level the normalised source counts flatten as a new population of faint radio sources emerge (Windhorst et al 1985). The dominance of starburst galaxies in the sub-mJy population is already well established (Gruppioni et al 2008), where the number of blue galaxies with star-forming spectral signatures is seen to increase strongly. , Hopkins et al (1998), and others have concluded that the source counts at these faintest levels require two populations, AGNs and starburst galaxies.…”
Section: Differential Countsmentioning
confidence: 94%
“…Radio loud sources dominate the source counts down to levels of ∼1 mJy, however, at the sub-mJy level the normalised source counts flatten as a new population of faint radio sources emerge (Windhorst et al 1985). The dominance of starburst galaxies in the sub-mJy population is already well established (Gruppioni et al 2008), where the number of blue galaxies with star-forming spectral signatures is seen to increase strongly. , Hopkins et al (1998), and others have concluded that the source counts at these faintest levels require two populations, AGNs and starburst galaxies.…”
Section: Differential Countsmentioning
confidence: 94%
“…sensitive to, for example, the 'discretization' of the template grids used in the fitting procedure. The systematic uncertainties on stellar masses and far infrared luminosities are likely to be around 0.3 dex (Gruppioni et al 2008;Mancini et al 2011;Santini et al 2015). As L IR,SF is important for our interpretation we also tested how reliable our values are for the targets that lack far infrared photometric detections, by re-fitting all of the other SEDs (with good FIR coverage) but removing the longer wavelength data.…”
Section: Star-formation Rates and Sed Fittingmentioning
confidence: 99%
“…Radio loud sources dominate the source counts down to levels of ∼1 mJy, however, at the sub-mJy level the normalised source counts flatten as a new population of faint radio sources emerge (Windhorst et al 1985). The dominance of starburst galaxies in the sub-mJy population is already well established (Gruppioni et al 2008), where the number of blue galaxies with star-forming spectral signatures is seen to increase strongly. Rowan-Robinson et al (1993), Hopkins et al (1998), and others have concluded that the source counts at these faintest levels require two populations, AGNs and starburst galaxies.…”
Section: Differential Countsmentioning
confidence: 93%